Store-operated calcium entry is reduced in spastin-linked hereditary spastic paraplegia - Winner, Beate; Rizo Garza, Tania; Gebhardt, Lisa; Riedlberger, Julia; Eberhardt, Esther; Fester, Lars; Alansary, Dalia; Winkler, Jürgen; Turan, Sören; Arnold, Philipp; Niemeyer, Barbara; Fischer, Michael (2022)
Pathogenic variants in SPAST, the gene coding for spastin, are the single most common cause of hereditary spastic paraplegia, a progressive motor neuron disease. Spastin regulates key cellular functions, including microtubule-severing and endoplasmic reticulum-morphogenesis. However, it remains unclear how alterations in these cellular functions due to SPAST pathogenic variants result in motor neuron dysfunction. Since spastin influences both microtubule network and endoplasmic reticulum structure, we hypothesized that spastin is necessary for the regulation of Ca2+ homeostasis via store-operated calcium entry. Here, we show that the lack of spastin enlarges the endoplasmic reticulum and reduces store-operated calcium entry. In addition, elevated levels of different spastin variants induced clustering of STIM1 within the endoplasmic reticulum, altered the transport of STIM1 to the plasma membrane and reduced store-operated calcium entry, which could be rescued by exogenous expression of STIM1. Importantly, store-operated calcium entry was strongly reduced in induced pluripotent stem cell-derived neurons from hereditary spastic paraplegia patients with pathogenic variants in SPAST resulting in spastin haploinsufficiency. These neurons developed axonal swellings in response to lack of spastin. We were able to rescue both store-operated calcium entry and axonal swellings in SPAST patient neurons by restoring spastin levels, using CRISPR/Cas9 to correct the pathogenic variants in SPAST. These findings demonstrate that proper amounts of spastin are a key regulatory component for store-operated calcium entry mediated Ca2+ homeostasis and suggest store-operated calcium entry as a disease relevant mechanism of spastin-linked motor neuron disease.Rizo et al. use iPSC-derived neurons from patients to investigate how pathogenic variants in SPAST give rise to hereditary spastic paraplegia. They show that dysregulation of spastin, a microtubule- and ER-remodelling protein encoded by SPAST, alters the dynamics of the ER, resulting in aberrant Ca2+ regulation.
Keywords: spastin; STIM1; microtubules; endoplasmic reticulum; store-operated calcium entry